UK universities compliance with the Concordat to Support Research Integrity: findings from cross-sectional time-series - Wager,Elizabeth (PeerJ, 2019)
Background The Concordat to Support Research Integrity published in 2012 recommends that UK research institutions should provide a named point of contact to receive concerns about research integrity (RI). The Concordat also requires institutions to publish annual RI statements. Objective To see whether contact information for a staff member responsible for RI was readily available from UK university websites and to see how many universities published annual RI statements. Methods UK university websites were searched in mid-2012, mid-2014 and mid-2018. The availability of contact details for RI inquiries, other information about RI and, specifically, an annual RI statement, was recorded. Results The proportion of UK universities publishing an email address for RI inquiries rose from 23% in 2012 (31/134) to 55% in 2018. The same proportion (55%) published at least one annual RI statement in 2018, but only three provided statements for all years from 2012/13. There was great variation in the titles used for the staff member with responsibility for RI which made searching difficult. Conclusion Over 6 years after the publication of the Concordat to Support Research Integrity, nearly half of UK universities are not complying with all its recommendations and do not provide contact details for a staff member with responsibility for RI or an annual statement.
Keywords: Research integrity; Misconduct; Universities; UK